Plasma concentrations of second-line antituberculosis drugs in relation to minimum inhibitory concentrations in multidrug-resistant tuberculosis patients in China: a study protocol of a prospective observational cohort study - Davies Forsman, Lina; Niward, Katarina; Hu, Yi; Zheng, Rongrong; Zheng, Xubin; Ke, Ran; Cai, Weiping; Hong, Chao; Li, Yang; Gao, Yazhou; Werngren, Jim; Paues, Jakob; et al. (BMJ open, 2018)
IntroductionIndividualised treatment through therapeutic drug monitoring (TDM) may improve tuberculosis (TB) treatment outcomes but is not routinely implemented. Prospective clinical studies of drug exposure and minimum inhibitory concentrations (MICs) in multidrug-resistant TB (MDR-TB) are scarce. This translational study aims to characterise the area under the concentration–time curve of individual MDR-TB drugs, divided by the MIC for Mycobacterium tuberculosis isolates, to explore associations with markers of treatment progress and to develop useful strategies for clinical implementation of TDM in MDR-TB.Methods and analysisAdult patients with pulmonary MDR-TB treated in Xiamen, China, are included. Plasma samples for measure of drug exposure are obtained at 0, 1, 2, 4, 6, 8 and 10 hours after drug intake at week 2 and at 0, 4 and 6 hours during weeks 4 and 8. Sputum samples for evaluating time to culture positivity and MIC determination are collected at days 0, 2 and 7 and at weeks 2, 4, 8 and 12 after treatment initiation. Disease severity are assessed with a clinical scoring tool (TBscore II) and quality of life evaluated using EQ-5D-5L. Drug concentrations of pyrazinamide, ethambutol, levofloxacin, moxifloxacin, cycloserine, prothionamide and para-aminosalicylate are measured by liquid chromatography tandem-mass spectrometry and the levels of amikacin measured by immunoassay. Dried blood spot on filter paper, to facilitate blood sampling for analysis of drug concentrations, is also evaluated. The MICs of the drugs listed above are determined using custom-made broth microdilution plates and MYCOTB plates with Middlebrook 7H9 media. MIC determination of pyrazinamide is performed in BACTEC MGIT 960.Ethics and disseminationThis study has been approved by the ethical review boards of Karolinska Institutet, Sweden and Fudan University, China. Informed written consent is given by participants. The study results will be submitted to a peer-reviewed journal.Trial registration number NCT02816931; Pre-results.